Rancang Bangun Aplikasi Penjualan Dan Pembelian Pada CV. Delta Computindo - Putro, Candra Dwi Wicaksono; Amelia, Tan; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Delta Computindo CV is a company engaged in the sale of computer equipment and the purchase of computer equipment from suppliers. CV Delta Computindo currently has four parts, the manager of the office, warehouse, purchasing, sales and administration, each office has a role and responsibility for each job. Recording of transactions must be recorded in detail because otherwise it will be difficulties in processing the data and the data that is already too much need a container to collect the data. Based on the above problems, it would require an application of sales and purchases to help the sales department in preparing reports and notifications to customers who want maturing loans, part of the purchase is expected to help the timely payment of the debt in order to not have to pay interest.